Alpha-Synuclein Induced Immune Cells Activation and Associated Therapy in Parkinson’s Disease - Su, Ruichen; Zhou, Tian (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) is a neurodegenerative disorder closely related to immunity. An important aspect of the pathogenesis of PD is the interaction between α-synuclein and a series of immune cells. Studies have shown that accumulation of α-synuclein can induce an autoimmune response that accelerates the progression of PD. This study discusses the mechanisms underlying the interaction between α-synuclein and the immune system. During the development of PD, abnormally accumulated α-synuclein becomes an autoimmune antigen that binds to Toll-like receptors (TLRs) that activate microglia, which differentiate into the microglia type 1 (M1) subtype. The microglia activate intracellular inflammatory pathways, induce the release of proinflammatory cytokines, and promote the differentiation of cluster of differentiation 4 + (CD4 +) T cells into proinflammatory T helper type 1 (Th1) and T helper type 17 (Th17) subtypes. Given the important role of α-synuclein in the immune system of the patients with PD, identifying potential targets of immunotherapy related to α-synuclein is critical for slowing disease progression. An enhanced understanding of immune-associated mechanisms in PD can guide the development of associated therapeutic strategies in the future.